Analysis of bearing failures in a typical high-power marine gearbox. Issue 1 (8th January 2018) - Gu, Haigang; Feng, Guang; Lin, Yonggang; Wang, Chaozhu
Abstract : Purpose: This paper aims to analyze fatigue failures of a typical marine gearbox under harsh ocean conditions, and these failures are reasonably attributed to the bearing fretting fatigue damages. Design/methodology/approach: Two typical FAG cylindrical roller bearings mounted on this marine gearbox are particularly used for analysis, as they are most vulnerable to these failures. A series of simulations have also been conducted to verify the analysis results and failure reasons by reproducing the fretting fatigue damages for the same shaft-bearing system under the same manufacturing error conditions. Findings: The analysis results indicate that manufacturing errors are the most possible reasons for the bearing failures, and these errors have more effects on the FAG cylindrical roller bearing as compared to other bearings mounted on the same shaft system. The simulations results are in good agreement with the theoretical analysis results and test results and hence validate that manufacturing errors are the dominant reasons for bearing fretting fatigue damages in this typical marine gearbox. Originality/value: Fatigue failures of a typical marine gearbox. Manufacturing errors are the most possible reasons for the bearing failures. A series of simulations have been conducted to verify the analysis results and failure reasons. The simulations results are in good agreement with the theoretical analysis results and test results.